CHANGING THE VECTORS OF INTERNATIONAL ACADEMIC COOPERATION MEETING THE NEEDS OF EXTERNAL AND INTERNAL STAKEHOLDERS - A. Gorylev; L. Alieva; V. Alieva; V. Samoylenko; E. Fomina (Вестник Северо-Кавказского федерального университета, 2022)
One of the cutting-edge trends in the internationalization of education is the development and implementation of international joint educational programs. In this regard, the authors consider the changes in geographical vectors of international cooperation of Russian universities on the example of joint educational programs. This article provides a comprehensive analysis of the needs of the main stakeholders of international joint educational programs: countries, universities, students, teachers and employers. The article presents the experience of Lobachevsky National Research University and North Caucasus Federal University. The example of these universities demonstrates the shift of the vector towards the activation of academic cooperation with CIS countries.